If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 1 = 5y + -7 Reorder the terms: 1 + 2g = 5y + -7 Reorder the terms: 1 + 2g = -7 + 5y Solving 1 + 2g = -7 + 5y Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2g = -7 + -1 + 5y Combine like terms: 1 + -1 = 0 0 + 2g = -7 + -1 + 5y 2g = -7 + -1 + 5y Combine like terms: -7 + -1 = -8 2g = -8 + 5y Divide each side by '2'. g = -4 + 2.5y Simplifying g = -4 + 2.5y
| (2x+7)+(5x-9)= | | 2(x+1)/3=3x-3 | | 5t=-1+6t | | 6x-82=8x-18 | | 1/3+1/4=5/12 | | d/4=-34 | | v/11.2=7 | | 90-g=125 | | 63=9-9n | | 9x-81=27 | | v-5=8 | | 6u^2-24u= | | 90l-g=15 | | 24=8/3w | | 7-7x=3x^2+5x+2 | | 7-12x=-2 | | -8=2+w | | 0=-2x^2+3 | | 2.2x+0.8x-5=4x | | 6-a=1/3(9a-18) | | 14x+12=7x+46 | | 5+2(x-1)=14 | | g(1)=-1 | | 20x-10x=30 | | 4g+4(-7+3g)=1-6 | | 10=w-6 | | 3(x-2)+5=7+x | | 2t-4v=-kv+8 | | q+3=10 | | 20x-10y=30fory | | h(2)=7 | | 5x-5=30x+15 |